Analisis Strategi Branding Kopi Bawang Dayak dalam Membangun Daya Saing Produk Lokal Unggulan - Pingkan Ade Sefiana; Meylan Damayanti Magdalena Simanjuntak; Anita Oktaviani Ningrum; Nandha Narendra Muvano (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
This study aims to analyze rebranding strategies and marketing communication in building the brand equity of Kopi Bawang Dayak as a regional flagship product. Kopi Bawang Dayak is a local product innovation based on the indigenous wisdom of Kalimantan that has functional and economic potential; however, it still faces challenges such as weak brand identity, unclear positioning, and ineffective marketing communication. This research adopts a qualitative approach using a descriptive method. Data collection techniques include interviews with business actors and consumers, observations of visual identity and promotional media, documentation, and literature review. The results indicate that rebranding strategies implemented through logo updates, packaging redesign, and the reinforcement of local values are able to enhance brand awareness and brand associations among consumers of Kopi Bawang Dayak. Furthermore, marketing communication that emphasizes storytelling, health benefits, and local cultural values through social media contributes to increasing perceived quality and building consumer trust. The synergy between rebranding strategies and marketing communication is proven to play a significant role in strengthening the brand equity of Kopi Bawang Dayak. This study concludes that integrating local identity with modern marketing approaches is a key factor in enhancing the competitiveness of regional flagship products in broader markets.